2021
DOI: 10.3390/en14020455
|View full text |Cite
|
Sign up to set email alerts
|

An Open-Source Monte Carlo Ray-Tracing Simulation Tool for Luminescent Solar Concentrators with Validation Studies Employing Scattering Phosphor Films

Abstract: Luminescent solar concentrators enhance the power output of solar cells through wave-guided luminescent emission and have great potential as building-integrated photovoltaics. Luminescent solar concentrators with a variety of geometries and absorbing–emitting materials have been reported in the literature. As the breadth of available experimental configurations continues to grow, there is an increasing need for versatile Monte Carlo ray-tracing simulation tools to analyze the performance of these devices for s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 26 publications
(60 reference statements)
0
5
0
Order By: Relevance
“…open-source ray tracing software capable of simulating a variety of 3D geometries, conducting validation studies on planar and wedge-shaped LSCs with scattering phosphor films. 64 However, the most widely used open-source ray tracing software for LSCs is pvTrace, 65,66 which has previously been used to model rectangular LSCs 43,65,67,68 and cylindrical/fiber LSCs. 69,70 It has also been used to study more unconventional geometries, such as luminescent solutionfilled cuvettes, 71 luminescent photo-microreactors, 72 LSCs with aligned nanorods, 73 the electric mondrian TM , 74 and PV leaf roof tiles.…”
Section: Smith Et Al Published a Versatilementioning
confidence: 99%
“…open-source ray tracing software capable of simulating a variety of 3D geometries, conducting validation studies on planar and wedge-shaped LSCs with scattering phosphor films. 64 However, the most widely used open-source ray tracing software for LSCs is pvTrace, 65,66 which has previously been used to model rectangular LSCs 43,65,67,68 and cylindrical/fiber LSCs. 69,70 It has also been used to study more unconventional geometries, such as luminescent solutionfilled cuvettes, 71 luminescent photo-microreactors, 72 LSCs with aligned nanorods, 73 the electric mondrian TM , 74 and PV leaf roof tiles.…”
Section: Smith Et Al Published a Versatilementioning
confidence: 99%
“…[ 2,3 ] If efficiently harvested and stored, [ 4–6 ] solar energy represents the most promising renewable energy source to satisfy building energy demands; [ 7,8 ] however, despite the increasing penetration of PV solutions, serving purposes ranging from water decontamination to electricity production, [ 9–11 ] building‐integrated photovoltaics (BIPV) have remained a relatively niche market. [ 12 ]…”
Section: Introductionmentioning
confidence: 99%
“…[2,3] If efficiently harvested and stored, [4][5][6] solar energy represents the most promising renewable energy source to satisfy building energy demands; [7,8] however, despite the increasing penetration of PV solutions, serving purposes ranging from water decontamination to electricity production, [9][10][11] buildingintegrated photovoltaics (BIPV) have remained a relatively niche market. [12] Since BIPV solutions directly replace building elements they must provide insulation value and structural integrity, while still functioning as PV devices that harvests energy efficiently. [13] The work of Bonomo et al [12] underlines that due to their architectural flexibility (higher esthetic appearance and the lower cost per square meter), 44% of BIPV products installed on building facades are thin-film solutions, despite they are less energy efficient if compared to crystalline systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhang et al reported an open-source Monte Carlo ray-tracing software with a graphical user interface (GUI) to model conventional rectangular LSCs, thus increasing accessibility to those unfamiliar with programming . Smith et al published a versatile open-source ray-tracing software capable of simulating a variety of 3D geometries, conducting validation studies on planar and wedge-shaped LSCs with scattering phosphor films . However, the most widely used open-source ray-tracing software for LSCs is pvtrace, , which has previously been used to model rectangular ,, and cylindrical/fiber LSCs. , It has also been used to study more unconventional geometries, such as luminescent solution-filled cuvettes, luminescent photomicroreactors, LSCs with aligned nanorods, the electric mondrian, and PV leaf roof tiles .…”
Section: Introductionmentioning
confidence: 99%